Growth dynamics, reproductive biology, and nutritional profiling of the freshwater mussel Lamellidens marginalis (Lamarck, 1819): implications for wild stock conservation and sustainable aquaculture development - Md. Mostafizur Rahman Mondol; Dil Afroz Nahar; Md. Ayenuddin Haque; Sumaya Akter Tisha; Md. Raihan Ali; Saleha Jasmine; Noorashikin Md Noor; Simon Kumar Das; Takaomi Arai; Bilal Ahamad Paray; Mohammad Belal Hossain; Mohammad Belal Hossain (Frontiers in Sustainable Food Systems)
Understanding the reproductive cycle ensures sustainable cultivation practices and facilitates effective management strategies to conserve natural stocks. Lamellidens marginalis, commonly available in South Asian countries, plays an essential role in the aquatic food chain. This study investigated the growth indices and reproductive activity of L. marginalis from a freshwater lake, aiming to understand its stock structure and sustainable exploitation rate. Furthermore, nutritional profiling of tissue was conducted to assess its potential for aquaculture. The results revealed significant variations in the mean biometric parameters across genders and periods. Compared with males, females presented numerically greater dimensions in all body measurements, except for shell height. The overall relationship between body weight and shell length indicated negative allometric growth (‘b’ values ranged between 2.430 and 3.156 for males and between 1.506 and 2.792 for females). The condition index exhibited significant seasonal fluctuations, with a rapid increase during April and June and a sharp decrease in July–August, potentially linked to gonadal maturation and spawning. Histological examination revealed a significantly male-dominated mussel population with an overall sex ratio of 1:0.89 (male: female). However, the histological analysis did not identify sexually undifferentiated and hermaphroditic individuals. This species displayed a continuous reproductive ability year-round, with a peak in July–August at 32.30−34.50°C. L. marginalis has the potential to be an excellent food source for animal on the basis of its nutritional values, and its biochemical composition was closely linked with reproductive activity. The outcomes of this study will guide the sustainable conservation of natural populations and the use of this species in aquaculture.